Numerical investigation of the combined effect of injection angle and injection pressure in a gasoline direct injection rotary engine. (1st September 2022) - Chang, Ke; Ji, Changwei; Wang, Shuofeng; Yang, Jinxin; Wang, Huaiyu; Xin, Gu; Meng, Hao
Abstract: This study aims to explore the combined effect of injection angle and injection pressure in a gasoline direct injection rotary engine through numerical simulation. Simulation results show that with the increase of injection angle, the fuel impinging position changes from the rotor recess to the middle cylinder block. At the same injection angle, the fuel enrichment area turns to the front of the combustion chamber with the increase of injection pressure. The lower injection angle is helpful to obtain a more uniform fuel distribution. Especially, with increase of injection pressure, the in-cylinder inhomogeneity index presents a downward trend. Under different injection pressures, the flame propagation period of the 0° injection angle is the most stable. The stable flame development and propagation processes make it easy to obtain higher indicated thermal efficiency. The highest indicated thermal efficiency is obtained at 0° injection angle and 15 MPa injection pressure, which is up to 24.99%. Moreover, compared with the fuel intake port injection, part of direct injection strategies help to get higher in-cylinder peak pressure. The higher in-cylinder temperature promotes the formation of NOx, but the organization of the in-cylinder fuel distribution can effectively reduce CO and Soot emissions. Highlights: A rotary engine simulation model with gasoline direct injection was established and validated. The combined effects of injection angle and injection pressure were investigated. The lower injection angle can obtain higher in-cylinder pressure and indicated thermal efficiency. Lower in-cylinder inhomogeneity index is helpful to reduce Soot and CO emissions.